Proceedings of the Twenty-Fifth Annual ACM-SIAM Symposium on Discrete Algorithms 2013
DOI: 10.1137/1.9781611973402.118
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Two-Prover-One-Round Game and The Hardness of Connectivity Problems

Abstract: Optimizing parameters of Two-Prover-One-Round Game (2P1R) is an important task in PCPs literature as it would imply a smaller PCP with the same or stronger soundness. While this is a basic question in PCPs community, the connection between the parameters of PCPs and hardness of approximations is sometimes obscure to approximation algorithm community. In this paper, we investigate the connection between the parameters of 2P1R and the hardness of approximating the class of so-called connectivity problems, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Recently, Laekhanukit gave randomized reductions from 2P1R-Game to the following network connectivity problems: Rooted k-Connectivity, Vertex-Connectivity Survivable Network Design, and Vertex-Connectivity k-Route Cut [49]. His hardness results improve those in [18,14,19], and our Theorem 1.8 further strengthens his results.…”
Section: Almost-coloringsupporting
confidence: 58%
See 1 more Smart Citation
“…Recently, Laekhanukit gave randomized reductions from 2P1R-Game to the following network connectivity problems: Rooted k-Connectivity, Vertex-Connectivity Survivable Network Design, and Vertex-Connectivity k-Route Cut [49]. His hardness results improve those in [18,14,19], and our Theorem 1.8 further strengthens his results.…”
Section: Almost-coloringsupporting
confidence: 58%
“…His hardness results improve those in [18,14,19], and our Theorem 1.8 further strengthens his results. See [49] for details.…”
Section: Almost-coloringmentioning
confidence: 99%
“…For Min-Rep, the typical way to show hardness of approximation with factor g is via proving hardness of approximating of Max-Rep of factor O(g 2 ). This was indeed also the route taken in [Lae14]; due to the square loss in parameter from Max-Rep, for a gap of g in Min-Rep, the alphabet size and the maximum degree now become O(g 4 log 2 g) and O(g 2 log 2 g) respectively.…”
Section: Introductionmentioning
confidence: 61%
“…The above three problems are shown to be hard to approximate to within a factor of k δ for some small (implicit) constant δ > 0 in [CLNV14,CK12,CMVZ16]. In [Lae14], Laekhanukit formulated the reduction in terms of Min-Rep Label Cover and observed that one can make δ explicit if the degree and the alphabet size can be made explicit polynomials of the gap. More precisely, the following theorem, which is a restatement of Theorem 3.1 in [Lae14], captures the dependency between the alphabet size, the degree and the resulting connectivity parameter.…”
Section: Vertex-connectivity K-route Cut (Vc-krc) Problemmentioning
confidence: 99%
“…Cheriyan et al [7] showed that -DST admits no 2 log 1−ε n -approximation algorithm, for any ε > 0, unless NP ⊆ DTIME(2 polylog(n) ). Laekhanukit [23] showed that the problem admits no 1/2−ε -approximation for any constant ε > 0, unless NP = ZPP. Nevertheless, the negative results do not rule out the possibility of achieving reasonable approximation factors for small values of .…”
Section: Related Workmentioning
confidence: 99%